Aplikasi Untuk Al-Qur’an Audio Juz 30 Bagi Penyandang Tunanetra Menggunakan Voice Recognition Berbasis Android - Albertia Youlanda; Irma Salamah; Ade Silvia Handayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
People with visual impairment are one of the community groups that need special attention from the surrounding area, because this group experiences difficulties in social life. Not only that, blind people also experience difficulties in their daily lives due to their disabilities, such as reading and memorizing the Qur'an juz 30. The current media does not make it easy for blind people to be able to choose surahs and verses of the Qur'an ' juz 30 that you want to memorize randomly. Application for Al-Qur'an Audio Juz 30 for people with visual impairment using Android-based Voice Recognition is a solution to overcome the above problems. Application for Al-Qur'an Audio Juz 30 for people with visual impairments using Android-based Voice Recognition equipped with a speech recognition system or Google Speech API developed by Google to recognize various kinds of human voices as input commands to the application and use the Arduino UNO module as the main controller in a tool for processing data on an SD card that can be read by the DFPlayer module so that it can recite the surah and verses contained in Al-Qur'an Juz 30. The voice command mode of calling the Qur'an juz 30 can be used in two modes, namely the selection mode per surah and selection mode per verse. Besides this application has a voice notification feature as a reminder for blind people to memorize the Qur'an juz 30 every day. Test results on these applications and tools show that applications and tools designed to function properly